Proposed formula to predict dendrite arm spacing in metal casting - Proyitno, Dody; Hamzah, Esah; Mohd. Ghazali, Mohd. Zulkifli (1999)

(untitled)
Dendrite morphology can be observed during metal casting or welding. A convenient and widely used method to determine the effect of dendrite morphology on solidification is through measurement of dendrite arm spacing. There are many parameters, which can affect the dendrite arm spacing. In welding process for example, the parameters are melting temperature, solid (work piece) temperature and welding speed. It is very important to calculate and predict the dendrite arm spacing because it has significant effect on the mechanical properties of the metal. This paper described a theoretical study on the formula for dendrite arm spacing in metal casting and also described the crystal growth rate formula on welding. It was found that the new relationship or formula has very good agreement with the experimental data.